Obtenção e caracterização de nanocristais de celulose a partir da coroa do abacaxi - Coutinho, Luana Venâncio [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Currently, interest in the use of natural fibers has increased due to environmental concern and consequent search for sustainable and renewable materials. Brazil is the second largest pineapple's producer, and after it was used in the industry, it generates approximately 45% of its initial weight in wastes, mostly the peel and the crown, that are often inadequate dispose, causing environmental damage. The objective of this work was to use the crown of the pineapple (Ananas comosus) to obtain cellulose nanocristals from acid hydrolysis with sulfuric acid (H2SO4) and hydrochloric acid (HCl) and different reaction time and acid concentration, adding value with an application to the waste and collaborating to reduce the environmental pollution generated from its disposal. The pineapple crown was oven dried for 24 h at 60 ºC, grounded and subjected to the following chemical pretreatment steps to remove amorphous components: alkaline treatment (NaOH solution 4% (w/v), 1 h at 70 ° C), two bleaching steps (solution of 300 mL of 4% NaOH (w/v) and 30 mL of 30% (v/v) H2O2 for 3 h) and alkaline treatment with KOH (KOH solution 4% (w/v) in the ratio of 1: 20 (g/mL) for 1 h at 80 ° C) resulting in bleached cellulose (CB). The CB was characterized by scanning electron microscopy (SEM), thermogravimetry (TGA), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (DRX), and it was submitted to different acid hydrolysis conditions changing the reaction time (30 min, 1 h, 2 h e 3 h), acid's type (sulfuric and hydrochloridric) and acid concentration (20%, 36%, 50% e 64%), in order to obtain nanocellulose (NC). NCs were characterized by zeta potential, TGA, FTIR, XRD and transmission electron microscopy (TEM). Chemical pre-treatments were efficient in the removal of amorphous components, and increased the fiber whiteness and the ... (Complete abstract click electronic access below)

Atualmente, o interesse pela utilização das fibras naturais tem aumentado devido à preocupação com o meio ambiente e consequente busca por materiais sustentáveis e renováveis. O Brasil é o segundo maior produtor mundial de abacaxi, produto que depois de ser usado na indústria, gera aproximadamente 45% do seu peso inicial em resíduos, incluindo a casca e a coroa, que são muitas vezes descartados de forma inadequada gerando danos ambientais. O objetivo desse trabalho foi utilizar a coroa do abacaxi (Ananas comosus) para a obtenção de nanocristais de celulose a partir da hidrólise ácida com ácido sulfúrico (H2SO4) e ácido clorídrico (HCl) em diferentes concentrações e tempo de reação, agregando valor e gerando uma aplicação aos resíduos, visando colaborar com a diminuição da poluição ambiental gerada a partir de seu descarte. A coroa do abacaxi foi seca em estufa a 60 ºC por 24 h, triturada e submetida às seguintes etapas de pré-tratamento químico para remoção de componentes amorfos: tratamento alcalino (solução de NaOH 4% (m/v), 1 h a 70 ºC), duas etapas de branqueamento (solução de 300 mL de NaOH 4% (m/v) e 30 mL de H2O2 30 % (v/v) por um total de 3 h) e tratamento alcalino com KOH (solução KOH 4 % (m/v) na proporção de 1:20 (g/mL) por 1 h à 80ºC) resultando na celulose branqueada (CB). A CB foi caracterizada por microscopia eletrônica de varredura (MEV), termogravimetria (TGA), espectroscopia de infravermelho com transformada de Fourier (FTIR) e difração de raios X (DRX), e a mesma foi submetida a diferentes condições de hidrólise ácida variando o tempo de reação (30 min, 1 h, 2 h e 3 h), tipo de ácido (H2SO4 e HCl) e concentração do ácido (20%, 36%, 50% e 64%) para obtenção de nanocristais de celulose (NC). Os NCs obtidos foram caracterizadas por potencial zeta, TGA, FTIR, DRX ...(Resumo completo, clicar acesso eletrônico abaixo)
Obtaining and characterizing cellulose nanocrystals from the pineapple crown
Keywords: Nanocristais; Celulose; Hidrolise; Abacaxi; Nanopartículas